The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3847/1538-4357/aa709d
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Supergranule Parameters with Solar Cycles: Results from Century-long Kodaikanal Digitized Ca ii K Data

Abstract: The century-long Ca II K spectroheliograms from Kodaikanal Solar Observatory, India, has recently been digitised and calibrated. Applying a fullyautomated algorithm (which includes contrast enhancement and 'Watershed method') on this data, we have identified the supergranules and calculated the associated parameters, such as scale, circularity, fractal dimension. We have segregated the quiet and active regions and obtained the supergranule parameters separately for these two domains. In this way, we have isol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…The latter was proposed by, e.g., Crouch et al (2007), who sug- gested that random clustering of magnetic elements could trigger downflows on supergranulation scales. Recently, Chatterjee et al (2017) found evidence for a solar-cycle dependence of supergranular parameters (e.g., the cell size) in century-long Ca ii K observation records.…”
Section: Cork Simulationmentioning
confidence: 99%
“…The latter was proposed by, e.g., Crouch et al (2007), who sug- gested that random clustering of magnetic elements could trigger downflows on supergranulation scales. Recently, Chatterjee et al (2017) found evidence for a solar-cycle dependence of supergranular parameters (e.g., the cell size) in century-long Ca ii K observation records.…”
Section: Cork Simulationmentioning
confidence: 99%
“…Antonucci et al 1977;Ermolli et al 2009b;Dorotovic et al 2010;Chatzistergos et al 2016Chatzistergos et al , 2019bBarata et al 2018;Tlatov & Tlatova 2019, and references therein), the solar radius variations (Meftah et al 2018;Hiremath et al 2020), network cell properties (e.g. Berrilli et al 1999;Ermolli et al 2003;Chatterjee et al 2017;Raju 2018), photometric properties of disc features over the solar cycle (e.g. Ermolli et al 2007Ermolli et al , 2010, as well as for the purpose of reconstructing of irradiance variations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, digitisation of various archives (for a list of the available archives see Chatzistergos 2017) allowed starting extensive exploitation of historical Ca II K spectroheliograms (SHG, e.g. Ribes & Mein 1985;Kariyappa & Pap 1996;Foukal 1996Foukal , 1998Caccin et al 1998;Worden et al 1998;Zharkova et al 2003;Lefebvre et al 2005;Ermolli et al 2009a,b;Tlatov et al 2009;Bertello et al 2010;DorotoviÄŤ et al 2010;Sheeley et al 2011;Priyal et al 2014Priyal et al , 2017Chatterjee et al 2016Chatterjee et al , 2017. Overall, there are numerous published results from historical Ca II K images, which agree in some respects, but also show significant differences (see Ermolli et al 2018).…”
Section: Introductionmentioning
confidence: 99%